1999
DOI: 10.2151/jmsj1965.77.1b_183
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Global Soil Wetness Project Soil Moisture Simulations

Abstract: To produce a global soil moisture "data set," ten different land surface models were forced with meteorological observations for a two-year period for the Global Soil Wetness Project (GSWP). We compare observed plant-available soil moisture in the top 1-m soil layer to the same quantity generated by the models. Our soil moisture observations are from grasslands and agricultural regions in Russia, Illinois (USA), China, and Mongolia.None of the models does a good job of producing the actual soil moisture value… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
78
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(87 citation statements)
references
References 36 publications
8
78
1
Order By: Relevance
“…[5] Various model intercomparison projects [e.g., Entin et al, 1999;Guo and Dirmeyer, 2006] have indicated that LSMs are much better at simulating a ''soil moisture'' anomaly (i.e., deviation from the mean) than simulating the absolute value of soil moisture. However, changes in DS bg can be affected by snowmelt, permeability of frozen soil, runoff parameterization, and vegetation dynamics in Arctic regions.…”
Section: Introductionmentioning
confidence: 99%
“…[5] Various model intercomparison projects [e.g., Entin et al, 1999;Guo and Dirmeyer, 2006] have indicated that LSMs are much better at simulating a ''soil moisture'' anomaly (i.e., deviation from the mean) than simulating the absolute value of soil moisture. However, changes in DS bg can be affected by snowmelt, permeability of frozen soil, runoff parameterization, and vegetation dynamics in Arctic regions.…”
Section: Introductionmentioning
confidence: 99%
“…The JMA-SiB model seasonal changes in soil moisture at some in-situ observation points were reproduced qualitatively, but not quantitatively, as well as the other models participating in the Global Soil Wetness Project (GSWP) (Entin et al 1999). The JMA-SiB model is consistently close to the median of the GSWP models in the data series (Rodell and Famiglietti 1999).…”
Section: Soil Moisture and Runoffmentioning
confidence: 75%
“…Eliminating the ®rst of these extremes from the calculation reduces the coef®cient of variation to 0.42, and eliminating both reduces it to 0.20. According to Entin et al (1999), the magnitude of the differences among the GSWP models is typically similar to or larger than the magnitude of the differences between observations and any one model. Therefore, using an uncertainty coef®cient of 0.30, which is in the range of the coef®cients of variation computed earlier, is reasonable.…”
Section: Resultsmentioning
confidence: 99%